2007
DOI: 10.6063/motricidade.3(4).655
|View full text |Cite
|
Sign up to set email alerts
|

O método Pilates® sobre a resistência muscular localizada em mulheres adultas

Abstract: Ferreira, C.; Aidar, F.; Novaes, G.; Vianna, J.; Carneiro, A.; Menezes, L.; O método Pilates ® sobre a resistência muscular localizada em mulheres adultas. Motricidade 3(4): 76-81

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
26

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 24 publications
0
8
0
26
Order By: Relevance
“…On the other hand, the study by Nunes Junior et al 27 , reported a significant improvement in the postural alignment of healthy individuals after 36 Pilates sessions that lasted 1 hour each, three times a week. The postural effects of Pilates could be attributed to an increase in resistance and muscle strength, as verified by Ferreira et al 28 . In this study 28 , the authors analyzed the influence of Pilates on the resistance and flex strength during abdominal exercises performed by women.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…On the other hand, the study by Nunes Junior et al 27 , reported a significant improvement in the postural alignment of healthy individuals after 36 Pilates sessions that lasted 1 hour each, three times a week. The postural effects of Pilates could be attributed to an increase in resistance and muscle strength, as verified by Ferreira et al 28 . In this study 28 , the authors analyzed the influence of Pilates on the resistance and flex strength during abdominal exercises performed by women.…”
Section: Discussionmentioning
confidence: 55%
“…The postural effects of Pilates could be attributed to an increase in resistance and muscle strength, as verified by Ferreira et al 28 . In this study 28 , the authors analyzed the influence of Pilates on the resistance and flex strength during abdominal exercises performed by women. The program lasted 9 weeks and generated significant increase in strength and resistance of abdominal muscles.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The popularity of Pilates has stimulated the development of studies investigating its effectiveness, evaluating the effects of training programs on different parameters such as muscle strength and muscle endurance (1,2), lexibility (3,4), decreased pain (5,6), joint function restoration (5, 7) among others. Given the positive results, the method has been increasingly indicated and used in training and orthopedic rehabilitation programs, with emphasis on the rehabilitation of lower limbs (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…O grau de fortalecimento proporcionado pelo Pilates contribui para um melhor alinhamento postural, devido a uma melhor relação entre músculos agonistas e antagonistas, relacionados ao equilíbrio postural e articular, otimizando os quadros de escoliose. 31 Assim, provavelmente devido ao fato de que os exercícios do método Pilates recrutam a musculatura estabilizadora, especialmente os multifídios, foi evidenciado, na participante do estudo, um aumento de força dos músculos extensores de tronco, ao final da intervenção.…”
unclassified